The effect of anemia on serum hepcidin levels in patients with heart failure - Uysal, Betul Borku; Akbas, Feray; Denız, Gulhan Ipek; Uysal, Duygu; Uysal, Harun; Atmaca, Hanife Usta; Yuksel, Yasin; Aral, Hale; Cetın, Guven; M, Cem Ar; Erdenen, Fusun (Journal of Cardiology and Cardiovascular Medicine, 2019)
Background: Anemia is an accelerating problem among patients with heart failure (HF) and its presence is associated with more symptoms. In this study, we investigated whether anemia in heart failure was related to hepcidin concentration. Methods: 50 patients with heart failure and 20 healthy subjects with no history of a chronic illness including heart failure as control group, were included in the study. Heart failure was verified by echocardiography in each subject and patients were defined as ones with reduced ejection fraction (HFrEF) if EF ≤ 40% and with preserved ejection fraction (HFpEF) if EF 40% - 50%. Blood samples were taken from all patients after 10-12 hours fasting. Anemia assessment was performed according to World Health Organization (WHO) criterias. Results: There was a positive correlation between hepcidin concentration and urea, ferritin, hemoglobin, hematocrite, C-reactive protein (p < 0,05). Hepcidin concentrations of anemic heart failure patients were significantly lower than the non-anemic heart failure patients (p < 0,05). Conclusion: We found that serum hepcidin concentration in anemic patients with heart failure was lower than in heart failure patients without anemia. We believe that iron defiency occurs as a result of inflammatory process in heart failure and therefore hepcidin concentrations decrease as a response. However, long-term follow up studies are needed.